Pembelajaran Sistem Blok dan Konteks Belajar: Studi Empiris Hasil Belajar Siswa SMK PGRI 1 Kudus - Nur Aqmarina; Dian Fithra Permana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the influence of block learning and learning context on vocational high school students’ academic achievement, with learning interest as a moderating variable. The learning context in this study includes learning facilities and the learning environment. The research is motivated by the persistently low learning outcomes among vocational students nationally, and the need for a teaching strategy that is responsive to the characteristics of vocational learners. A quantitative approach with a correlational design was employed. Data analysis techniques included multiple regression and moderation analysis, using data from 49 students at SMK PGRI 1 Kudus as the sample. The results showed that block learning had a significant positive effect on student achievement. The learning environment also had a significant influence, whereas learning facilities did not show a significant effect. Learning interest was found to moderate the relationship between block learning and learning outcomes, but did not moderate the influence of learning facilities or the learning environment. Simultaneously, block learning, facilities, and environment contributed 56.2% to learning outcomes, increasing to 65.6% when learning interest was included in the model.This study highlights the importance of teaching approaches that go beyond instructional strategies to also incorporate contextual and psychological aspects of students. Practically, schools are encouraged to design instructional systems that integrate block learning models with efforts to foster student interest and create supportive learning environments.